Management Strategy Analysis in Pharmaceutical Companies: A Case Study of Generic Drug Manufacturers - nugraha, evan; Rini Mulyani Sari (Jurnal Manajemen (Edisi Elektronik), 2025)
MEA is the establishment of a free market in Southeast Asia with the goal of attracting international investment. Several factors contribute to Indonesia's ability to win AEC competition, including a big potential market and the possibility to become an exporting economy, particularly in the pharmaceutical business. However, numerous obstacles must be considered, according to government objectives, for the current situation of the Indonesian pharmaceutical sector to improve. The Indonesian pharmaceutical market has a lot of promise, but approximately 95% of medicinal raw materials will be imported. Becouse of that to attempted to analyze the aforementioned destination for strategy management using many methods, including SWOT, IFE and EFE, internal-external, and QSPM matrix. The gap in ratings, based on the data analysis results, indicates that the company's internal procedures need to be addressed. Internal improvement is a continual approach to the concept of continuous improvement that is used to carry out the strategy. Based on the above description, study on pharmaceutical firms is required to determine what techniques to enhance management systems may support smooth operations. This research was conducted at a pharmaceutical company that produces generic drug.